1 Corinthians - Nash, Scott, 1953- (Macon, Ga. : Smyth & Helwys Pub., 2009)
"Perhaps more than any other book in the New Testament, 1 Corinthians offers readers a window to the life of the early church. Through this window we catch a glimpse of a community of faith struggling with questions of identity, relationship, belief, and practice. Yet our vision through the window of 1 Corinthians is not without significant limitations. The author of 1 Corinthians, the apostle Paul, has framed the shape of the window. For the most part, we can see only what Paul wished to expose and only in the ways he wished to expose them. We cannot know beyond any doubt that his presentation of the situation was an accurate reflection of that situation, nor can we be certain that we even correctly understand what Paul presented ... the primary goal of the Smyth & Helwys Bible Commentary series is to make available serious, credible biblical scholarship in an accessible and less intimidating format. A visual generation of believers deserves a commentary series that contains not only the all-important textual commentary on Scripture, but images, photographs, maps, works of fine art, and drawings that bring the text to life. Each volume of the Smyth & Helwys Bible Commentary series features a CD-ROM, which expands the uses and capabilities of the Commentary even more"--Publisher description.
Straining upon the start, 1:1-9 -- Hearing the world of the cross : divisiveness in the church, 1:10-3:4 -- Serving together for the good of the church, 3:5-4:21 -- Disciplining the body, 5:1-6:20 -- Remaining as you are : sex, divorce, and marriage, 7:1-40 -- Eating food offered to idols, 8:1-9:27 -- Flee the worship of idols, 10:1-11:1 -- Problems in the context of worship, 11:2-34 -- Spiritual gifts and love, 12:1-14:40 -- The resurrection of the dead, 15:1-34 -- Final matters, 16:1-24.
Includes bibliographical references (pages 453-467) and indexes.
Print version record.
Keywords: Bible. -- Commentaries; Bible; RELIGION / Biblical Studies / New Testament; RELIGION / Biblical Studies / Paul's Letters; Commentaries; Electronic books